A Bronze Loop of an Early Carolingian Spur Set from Putalj above Kaštel Sućurac (Archaeologia Adriatica, 2010)
A bronze loop (a slot for running the spur strap through) of a spur set was found during the archaeological research of the cemetery near the church of St. George above Kaštel Sućurac. When the results of the research were published, it was not identified correctly. Instead it was interpreted as a gothic buckle in the catalogue. Nevertheless it is undoubtedly a loop of a strap set with a square frame and decorated front plate from the final 8th or the first half of the 9th century. A find that has been identified in this way can be easily interpreted in the context of the Putalj cemetery. Namely a layer of graves from the early 9th century was identified at Putalj. A find from Putalj is particularly important since such finds have not been previously known in the territory of the immediate hinterland of Split i.e. the Solin-Kaštela region, so that this fact was considered as a proof that the remaining late Antique population was still present in the mentioned territory. Besides the Putalj spur loop, there are two more similar finds from the Solin region published recently for the first time which do not speak in favor of this thesis. These are bronze loops belonging to spur sets of early Carolingian provenance confirming once more that presence of one such item at Putalj is not a coincidence. All three early Carolingian finds from the Solin-Kaštela region have direct analogies among the finds from princely graves from Crkvina in Biskupija. When Croatian territory entered Frankish sphere of interest by the end of the 8th century, Slavic population in the hinterland of the Dalmatian coast predominantly lived in a tribal-clan social system. Presence of rich graves testifies to a beginning of social stratification and commencements of feudalism. This process is evident in the entire territory in which the Croatian princedom was about to be formed during the 9th century. More significant concentration of the finds in question is noticable in the regions which were about to become important centers of the Croatian state (Nin, Ravni Kotari, Knin, Livno, and also the Solin Kaštela region). Early Carolingian finds from Putalj and Solin which are related to the original territory of the Trpimirović dynasty additionally confirm this thesis.
Keywords: Putalj; Solin; Biskupija-Crkvina; spurs; spur sets